STRATEGI DINAS SOSIAL, PEMUDA DAN OLAHRAGA KOTA SEMARANG (UPAYA PEMBERDAYAAN KEWIRAUSAHAAN BERBASIS CLUSTER)) - Yurita Kusuma Wardani; Hesti Lestari; Aloysius Rengga (Journal of Public Policy and Management Review, 2013)
Rising youth unemployment is fluctuating from year to year increasing, this condition will be a time bomb if it does not immediately get serious attention from the government. The stigma that arise in public life have an impact on the youth in the various facets of youth. Coupled with the absence of local regulations that protect the rights of the youth. This condition is the background of this research.The purpose of this study to determine the cluster-based youth empowerment and entrepreneurship obstacles or barriers faced by Department of Social Welfare, Youth and Sports of Semarang. The data obtained is then used to formulate alternative strategies that can be used in an effort to empower youth entrepreneurship.To reveal the problems of the purpose of the study, researchers used a qualitative approach using the analytic theory of strategic management. Data analysis was done using SWOT matrix and the Litmus Test.The results showed that in the effort to empower youth entrepreneurship-based clusters can not be said to be optimal, so we need a strategy to minimize the condition. From the litmus test results, strategic issues in cluster-based empowerment youth entrepreneurship is to increase the role of each stakeholder (Office, community leaders, youth organizations and training centers) to achieve freedom from unemployment Semarang. In the effort to empower youth entrepreneurship-based clusters, namely optimization advice given budget through cooperation with the private sector, improve the quality and quantity of human resources, and create a regulatory or legal basis and to increase public support.